The Law Enforcement Of Hate Speech Crime In Polda Lampung - Ridho Grisyan; Sunarto DM; Heni Siswanto (Ius Poenale, 2021)
Criminal acts related to hate speech are one of the crimes that occur as a result of the misuse of information technology carried out by a person or group by conveying forms of provocation, seditious actions, or in the form of insults to someone or certain other groups in terms of various indicators, namely race, skin, gender, religion and others. Research problems: how are the efforts to deal with the criminal act of distributing electronic information containing hate speech at POLDA Lampung and why there are obstacles to efforts to overcome the criminal act of distributing electronic information containing hate speech at the Regional Police located in Lampung Province. This type of research is a normative juridical research. The data analysis was done qualitatively. The approach to the problem used is the statute approach. The results of this study indicate that the law enforcement of hate speech using social media is carried out by the Sub-Directorate for Cyber Crime of POLDA Lampung through non-penal and penal means. Non-penal efforts are carried out by carrying out cyber patrols and socializing the prohibition on hate speech using social media. Penal efforts carried out by investigation and investigation. The factors that hinder efforts to overcome criminal acts of hate speech by using social media are in the aspects of legislation, aspects of law enforcement officials, facilities and infrastructure, community conditions and cultural aspects of these factors, there are dominant factors being weaknesses, namely in the aspect of law enforcers who are not yet competent and have mastered the development of types of crimes related to information technology, precisely at the Cyber Police Unit in Lampung Province.